Analysis and Implementation of The Riau Provincial Government Policy on Forests: Case Study: Governor Regulation Number 11 of 2014 Concerning the Forest and Land Fire Control Center - Afridinata Afridinata (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This research attempts to elaborate on the analysis and implementation of the Riau Provincial Government's policy on forests, using the case study of Governor Regulation Number 11 of 2014 concerning the Forest and Land Fire Control Center. The purpose of this research is to understand the content of the Riau Provincial Government's policy through Governor Regulation Number 11 of 2014 on the Forest and Land Fire Control Center and to analyze the Riau Governor Regulation of 2014 concerning the Forest and Land Fire Control Center. To analyze this study, the data used in this research are sourced from books, archives, documents, the internet, and interviews. The analytical method applied in this research is a qualitative descriptive method, which involves creating, describing, and summarizing various conditions with the variables emerging from the research object and revealing facts through data collection, which are then studied, processed, analyzed, and interpreted to be presented descriptively. The theories used in this research include public policy, environmental politics, and development politics theories.